Formation of the state language as the language of the law - Tokatov, R.A.; Ilyassova, G.A. (Bulletin of the Karaganda University “Law Series”, 2023)
The article discusses the consequences of translating the text of laws into the state language after their development and adoption in the official Russian language in our country. The authors are convinced that raising the status of the state language is of paramount importance, acting as one of the principles that give stability to the sovereignty of the state. As is known, in law enforcement practice, difficulties arise in the application of incorrectly translated articles from Russian into Kazakh in the text of laws. As an example, the authors have identified some incorrect translations that do not correspond to the principle of authenticity in the texts of the Civil Code of the Republic of Kazakhstan (general part), the Civil Code of the Republic of Kazakhstan (special part), the Entrepreneurial Code of the Republic of Kazakhstan, the Law of the Republic of Kazakhstan “On Charity” in Russian and Kazakh, and offer correct translations in the state language in the texts of laws. It is concluded that the reason for the incorrect translations is the non-compliance in the legislative process with the requirements of legal technology, including the requirements of legal linguistics for the translation of legal terminology. The authors propose legal mechanisms for the formation of the state language as the language of the law, by analyzing the identified erroneous translations from the texts of laws in the Kazakh language. In conclusion, the necessity of solving the issue of the formation of the state language as the language of the law is justified only by establishing such a mechanism of legal regulation